(untitled) (The Pakistan Development Review, 2010)
Fiscal policy refers to government‟s efforts to influence the direction of the economy through changes in taxes or expenditures. Optimal fiscal policy in Pakistan and in other developing countries plays a pivotal role in growth process and, hence, serves as a vital instrument for economic growth. The efficacy of fiscal policy in improving economic conditions in the long run is, however, a controversial issue and needs further investigation. In conventional model, a federal tax cut without a corresponding reduction in federal expenditures will encourage consumption expenditures and interest earnings due to increase in personal disposable income. Contrarily, according to Ricardian Equivalence Theorem (RET), the same change in fiscal policy will not result in any of the above mentioned macroeconomic impacts. In other words, a reduction in deficit-financed federal tax cut will not affect macroeconomic outcomes [Saxton (1999)].